Dpal ʼBrug-pa rin po cheʼi bstan pa rgya cher rgyas par smon pa dpag bsam ljon paʼi dri bsuṅ źes bya ba bźugs so - Byams-me-lha-mchog Ṅag-dbaṅ-bstan-ʼdzin-blo-gros, b. 1843? (Rgod tshaṅ sgrub sde, 1971)
Prayer (praṇidhāna) for the propagation and triumph of the Drukpa Kargyudpa sect of Tibetan Buddhism.